2022
DOI: 10.1155/2022/1076053
|View full text |Cite|
|
Sign up to set email alerts
|

Curative Effect of Prebiotics/Probiotics-Assisted Ketogenic Diet on Children with Refractory Epilepsy

Abstract: Objective. The aim is to study the curative effect of prebiotics/probiotics-assisted ketogenic diet (KD) on children with refractory epilepsy. Methods. A retrospective analysis was performed on the clinical data of 80 children with refractory epilepsy treated in the hospital between December 2018 and December 2020. According to different treatment methods, they were divided into the KD group (36 cases, KD) and combination group (44 cases, prebiotics/probiotics assisted KD). All were followed up for 1 year. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, the incidence of adverse reactions was significantly decreased in the combination group. Although this was a retrospective analysis, the study implied that probiotics may greatly assist KDs in the treatment of patients with DRE [ 163 ].…”
Section: Potential Dietary Treatments: Pro/prebioticsmentioning
confidence: 99%
“…Moreover, the incidence of adverse reactions was significantly decreased in the combination group. Although this was a retrospective analysis, the study implied that probiotics may greatly assist KDs in the treatment of patients with DRE [ 163 ].…”
Section: Potential Dietary Treatments: Pro/prebioticsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%